Analisa Input Output Sektor Pariwisata Di Kabupaten Banyuwangi - Muhamad Annas (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2018)
This study aims to (1) identify linkages of the tourism sector in various economic sectors, (2) to identify the impact of the tourism sector to the economic sector in the views from the output multiplier and income multiplier. These results indicate that the sectors that have relevance to the future (forward linkage) is highest with the agriculture and fisheries sector linkages value directly ahead of 0.6150 and indirect linkages at 1.3429. While the sector has backward linkages (backward linkage), the highest is the manufacturing sector with a value of backward linkages directly at 0.6960 and indirect linkages at 1.0963. Judging from the scatter forward and backward the highest of the tourism sector is a sector group of the restaurant, that is equal to 1.0058 and 1.1364 (DSD> 1; DSB> 1). The coefficient multiplier output is the highest type I is the agricultural sector and the results with a coefficient of 1.958. For type II multiplier output which has the highest coefficient is the livestock sector and fisheries amounted to 2,599. The manufacturing sector is the sector that has the income multiplier coefficients Type I as the highest, 1,874. Meanwhile, for Type II income multiplier of social and community services sector became the sector that has the highest coefficient is 2.392.